2015
DOI: 10.1002/marc.201500149
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly‐Driven Electrospinning: The Transition from Fibers to Intact Beaded Morphologies

Abstract: Polymer beads have attracted considerable interest for use in catalysis, drug delivery and photonics due to their particular shape and surface morphology. Electrospinning, typically used for producing nanofibers, can also be used to fabricate polymer beads if the solution has a sufficiently low concentration. In this work, we present a novel approach for producing more uniform, intact beads by electrospinning self-assembled block copolymer (BCP) solutions. This approach allows a relatively high polymer conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 61 publications
3
42
0
Order By: Relevance
“…There are many factors that influence the internal molecular structure and properties of electrospun nanofibres (i.e. flow rate of polymer solution, applied voltage, tip‐to‐collector distance, ambient parameters, polymer solution concentration, polymer molecular mass, viscosity, surface tension and conductivity), which in turn govern the end‐use of the nanofibres . Consequently, the effects of blend ratio and PCL molecular mass (PCL1 and PCL2) on morphology, miscibility, crystallinity, thermal properties, hydrophobicity and cell culture ability of the ternary blend electrospun nanofibres were studied.…”
Section: Resultsmentioning
confidence: 99%
“…There are many factors that influence the internal molecular structure and properties of electrospun nanofibres (i.e. flow rate of polymer solution, applied voltage, tip‐to‐collector distance, ambient parameters, polymer solution concentration, polymer molecular mass, viscosity, surface tension and conductivity), which in turn govern the end‐use of the nanofibres . Consequently, the effects of blend ratio and PCL molecular mass (PCL1 and PCL2) on morphology, miscibility, crystallinity, thermal properties, hydrophobicity and cell culture ability of the ternary blend electrospun nanofibres were studied.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, SEBS was dissolved in neat THF across a concentration range of 8 -20 wt% to produce beads or fibers. [36] Based on this work, a solution of 14 wt% SEBS was selected as an optimum concentration to make fibers. It had been reported that high humidity in addition to high solvent volatility often leads to the formation of pores on electrospun fibers.…”
Section: Fabrication Of Sebs Fibers and Beadsmentioning
confidence: 99%
“…[23,[27][28][29][30][31][32][33][34] Fibers, beads or beaded structures can be electrospun or electrosprayed from polymer solutions with low concentrations or low molecular weight, [35] or via specialized self-assembly driven electrospinning. [36] Both electrospinning and electrospraying operate using the principles of electrohydrodynamics, and are widely applied to fabricate superhydrophobic surfaces. For example, Jiang et al [1] prepared a lotus-leaf-like superhydrophobic surface from a composite film consisting of electrosprayed polystyrene (PS) microspheres (beads) and electrospun nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from electrospinning, the in situ cross-linkable system should also be compatible with other emerging methods to produce polymer nanofibers and nanoparticles, [17] such as centrifugal spinning [18][19][20][21] with scale-up possibilities. [20] In centrifugal spinning, the in situ crosslinkable system will be placed in a rotating spinning head and ejected into a liquid jet from the nozzle tip of the spinning head, when the rotating speed reaches the threshold that the centrifugal force overcomes the surface tension of the spinning fluid.…”
Section: Electrospinning and In Situ Cross-linkingmentioning
confidence: 99%